2010
DOI: 10.1002/pen.21655
|View full text |Cite
|
Sign up to set email alerts
|

Compatibilization of PP/PAE blends by means of the addition of an ionomer

Abstract: Minor amounts of poly(ethylene‐co‐methacrylic acid) ionomer neutralized with Zn (PEMA‐Zn) were added in the melt state to blends of polypropylene (PP) with up to 40% of poly(amino ether) (PAE) resin. Given the good barrier characteristics of PAE, it is a good candidate to improve the poor barrier properties of PP. However, PP/PAE blends were found to be almost fully immiscible, with a large dispersed phase size and a brittle mechanical behavior. Upon PEMA‐Zn addition, the dispersed particle size clearly decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 66 publications
2
2
0
Order By: Relevance
“…For all the blends, the glass transition temperatures are displaced from those of the neat components, which is in agreement with the results obtained by Granado et al 17 In the case of the T g corresponding to PCL phase, the addition of PHAE decreases the glass transition temperature. This behavior has been observed also in other PHAE blends; 13,36 actually, this fact has been attributed to the migration of a plasticizer from PHAE to the other polymer as it has been proved by Granado et al 36 Regarding the T g corresponding to PHAE phase, the temperature is also decreased considerably, in the range of 7 -16 depending on the composition, which clearly indicates that some amount of PCL is solubilized in the PHAE phase; therefore, the blends are partially miscible. Infrared spectroscopy measurements were carried out to analyze the interactions between PCL and PHAE; however, the carbonyl stretching region, see Figure 1 (values reported in Supporting Information Table S1) does not vary significantly with the incorporation of PHAE.…”
Section: Dynamic Mechanical Analysissupporting
confidence: 80%
See 1 more Smart Citation
“…For all the blends, the glass transition temperatures are displaced from those of the neat components, which is in agreement with the results obtained by Granado et al 17 In the case of the T g corresponding to PCL phase, the addition of PHAE decreases the glass transition temperature. This behavior has been observed also in other PHAE blends; 13,36 actually, this fact has been attributed to the migration of a plasticizer from PHAE to the other polymer as it has been proved by Granado et al 36 Regarding the T g corresponding to PHAE phase, the temperature is also decreased considerably, in the range of 7 -16 depending on the composition, which clearly indicates that some amount of PCL is solubilized in the PHAE phase; therefore, the blends are partially miscible. Infrared spectroscopy measurements were carried out to analyze the interactions between PCL and PHAE; however, the carbonyl stretching region, see Figure 1 (values reported in Supporting Information Table S1) does not vary significantly with the incorporation of PHAE.…”
Section: Dynamic Mechanical Analysissupporting
confidence: 80%
“…In the case of the T g corresponding to PCL phase, the addition of PHAE decreases the glass transition temperature. This behavior has been observed also in other PHAE blends; actually, this fact has been attributed to the migration of a plasticizer from PHAE to the other polymer as it has been proved by Granado et al . Regarding the T g corresponding to PHAE phase, the temperature is also decreased considerably, in the range of 7°–16° depending on the composition, which clearly indicates that some amount of PCL is solubilized in the PHAE phase; therefore, the blends are partially miscible.…”
Section: Resultssupporting
confidence: 64%
“…The addition of 5% of the compatibilizer increased the elongation at break from around 10% to greater than 300%. 17 The third strategy is to use intermolecular interactions such as hydrogen bonding [23][24][25][26][27] and ionic interactions [28][29][30] to strengthen the interface. A study by Hirai et al has shown a blend of polyamide 11 (PA11) and poly(vinylcatechol) (PVCa) exhibits excellent engineering properties due to the hydrogen bonding between PA11 and PVCa.…”
Section: Introductionmentioning
confidence: 99%
“…Common reactive functional groups include anhydride, epoxy, and isocyanate. [8][9][10][11][12][13][14] The third type of compatibilizer uses intermolecular interactions such as hydrogen bonding [15][16][17][18][19] and ionic interactions [20][21][22] to strengthen the interface.…”
Section: Introductionmentioning
confidence: 99%